Amyotrophic lateral sclerosis. Issue 10107 (4th November 2017) - van Es, Michael A; Hardiman, Orla; Chio, Adriano; Al-Chalabi, Ammar; Pasterkamp, R Jeroen; Veldink, Jan H; van den Berg, Leonard H
Summary: Amyotrophic lateral sclerosis is characterised by the progressive loss of motor neurons in the brain and spinal cord. This neurodegenerative syndrome shares pathobiological features with frontotemporal dementia and, indeed, many patients show features of both diseases. Many different genes and pathophysiological processes contribute to the disease, and it will be necessary to understand this heterogeneity to find effective treatments. In this Seminar, we discuss clinical and diagnostic approaches as well as scientific advances in the research fields of genetics, disease modelling, biomarkers, and therapeutic strategies.